Improving Wellness of Operating Room Personnel: A Light-Based Intervention on Perceived Nursing-Related Stress - Guerrier, Gilles; Margetis, Dimitri; Agostini, Christine; Machroub, Zakia; Di Maria, Sophie (Frontiers in Psychiatry, 2021)
Background: Nursing is an emotionally demanding and physically draining occupation. Wellbeing of health care workers is essential to achieve success in care and have good cooperation relationships with other health professionals. Objective: The purpose of this study was to evaluate the effectiveness of a light-based intervention on perceived nursing-related stress and job satisfaction in health care personnel working in an operating room environment. Methods: A total of 84 nurses participated in this randomized, cross-over controlled study. Intervention consisted of 4 weeks of bright blue-enriched light exposure using a LED head-mounted portable device (n=42) or no light exposure (n=42) separated by a 2-week washout period in a crossover fashion. Participants completes questionnaires for the Nursing Stress Scale (NSS). Results: Intervention and control groups were comparable in terms of demographics, with a median age of 34 (IQR: 27–49) and 69 (84%) female. The 84 participants had a median age of 34 (IQR: 27–49), and 69 (82%) of them were female. The mean baseline NSS score was similar in both groups before intervention during the AB period: 83.5 (SD 8.1)] and 84.3 (SD 8.3) in the control group and the intervention group, respectively (p=0.7). No significant difference was seen in the mean NSS scores after intervention in control groups: the NSS score difference before and after intervention was 1.4 (SD 8.4) (p=0.16) and 1.7 (SD 8.9) (p=0.12) during periods AB and BA, respectively. The NSS score of the intervention group was significantly lower after intervention than the baseline score: the NSS score difference before and after intervention was 15.1 (SD 7.6) (p<0.001) and 19.7 (SD 7.5) (p<0.001) during periods AB and BA, respectively. The cross group comparison after intervention showed a significantly higher NSS score difference after intervention in the intervention group than the control group: 15.1 (SD 7.6) vs 1.4 (SD 8.4) (p<0.001) and 19.7 (SD 7.5) vs 1.7 (SD 8.9) (p<0.001) during periods AB and BA, respectively. Conclusion: Alternative person-directed initiatives should be considered to improve the wellbeing of the health workforce, especially during the coronavirus pandemic.